A NEW SPECIES OF BALCANOCERUS MALDONADO-CAPRILES (HEMIPTERA: AUCHENORRHYNCHA: CICADELLIDAE: EURYMELINAE) FROM EASTERN ANATOLIA, WITH A KEY TO PALAEARCTIC SPECIES AND NEW RECORDS - Gnezdilov, Vladimir M.; Ozgen, Inanc (Entomol Soc Washington, 2021)
Balcanocerus stellatus new species, occurring on Prunus (Amygdalus) dulcis (Mill.) D. A. Webb, is described from Elazig Province, Turkey. Balcanocerus amygdali (Korolevskaya, 1968) and B. amygdalicolus Dlabola, 1994 are reported for the first time from Turkmenistan, which are the first records for these species other than the type localities, and new records are provided for Balcanocerus balcanicus (Horvath, 1903) from Elazig Province. A key to the males of the Palaearctic species of the genus Balcanocerus Maldonado-Capriles, 1971 is provided.
Keywords: Idiocerini; morphology; distribution; taxonomy